Note - Carthy, A. E.
035-0138-001 NOTE. 4th September, 1942. I telephoned to Mr. Palmer of the Co-operative Party, Victoria Street, with regard to the letter which we received from the Birmingham and District Co-operative Party concerning the position of former members of the International Brigade who are interned in France, Spain and North Africa. I told him that the communication had been addressed to the National Council of Labour and he agreed to deal with the matter, if I sent him a copy of the letter. I explained the position on the lines of the reply which we normally send to enquiries which we receive, and he agreed to deal with the enquiry, on the understanding of course that the Co-operative Party central office would be able to raise this issue in the N.C.L. if they so desire. A.E.C. 292/946/35/138